2005
DOI: 10.1002/aoc.1001
|View full text |Cite
|
Sign up to set email alerts
|

Simple and economical conversion of organic compounds with H2O2 catalyzed by ruthenium (III) chloride

Abstract: Six aromatic aldehydes, two hydrocarbons, one cycloalcohol and one aromatic alcohol, viz. benzaldehyde, p-chlorobenzaldehyde, cinnamaldehyde, 4-methoxybenzaldehyde, o-hydroxybenzaldehyde, 4-hydroxy, 3-methoxybenzaldehyde, anthracene, phenanthrene, cyclohexanol and benzyl alcohol dissolved in acetic acid, were oxidized in quantitative to moderate yields by 50% H 2 O 2 in the presence of traces of RuCl 3 (substrate : catalyst ratio 85 400 to 387 500 : 1). Conditions for highest yields, under most economical cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…However, reactions in alkaline medium [1][2][3][4][5][6][7][8] are not fast probably due to the reduced oxidation potential of the [Fe(CN) 6 ] 3− /[Fe(CN) 6 ] 4− redox couple. 9 It is for this reason that a large number of transition metal ions such as Os(VIII), [10][11][12][13] Ru(III), [14][15][16][17] Ru(VI), 18 Ru(IV), 19 Rh(III), 20 Ir(III), 21 Ru(VIII) 22 and Pd(II) 23,24 have been employed as catalysts in alkaline medium. A large number of Os(VIII)-catalysed oxidations of both organic [25][26][27][28][29][30] and inorganic [31][32][33] compounds with hexacyanoferrate(III) in alkaline media have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…However, reactions in alkaline medium [1][2][3][4][5][6][7][8] are not fast probably due to the reduced oxidation potential of the [Fe(CN) 6 ] 3− /[Fe(CN) 6 ] 4− redox couple. 9 It is for this reason that a large number of transition metal ions such as Os(VIII), [10][11][12][13] Ru(III), [14][15][16][17] Ru(VI), 18 Ru(IV), 19 Rh(III), 20 Ir(III), 21 Ru(VIII) 22 and Pd(II) 23,24 have been employed as catalysts in alkaline medium. A large number of Os(VIII)-catalysed oxidations of both organic [25][26][27][28][29][30] and inorganic [31][32][33] compounds with hexacyanoferrate(III) in alkaline media have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, anthraquinones have been widely used as catalysts for producing hydrogen peroxide [15], dyes for fibers [16,17] and cells [18], a digestion catalyst for wood [19], and chemical sensors [20]. Thus, the development of synthetic methods for the formation of multi-substituted anthraquinones is an important research topic, and several synthtic methods including the oxidation of anthracene [21,22], the Friedel-Crafts reaction of phthalic anhydride [23], and the Diels-Alder reaction of naphthoquinones followed by aromatization [24] have been developed.…”
Section: Introductionmentioning
confidence: 99%
“…We have also reported the oxidation of cyclic ketones by alkaline hexacyanoferrate(III) catalyzed by rhodium(III) chloride, in which it was observed that the catalytically active species of rhodium(III) depends on the pH of the medium [6,7]. We have also compared the catalytic activity of rhodium(III) chloride with iridium(III) and palladium(II) in the oxidation of various organic compounds with hydrogen peroxide from the synthetic point of view and it was observed that rhodium(III) is quite effective in catalyzing the such as organic oxidations [8]. To find out the potential of rhodium(III) chloride in catalyzing the oxidation of vicinal diols with cerium(IV) sulfate, in aqueous sulfuric acid medium, and to confirm whether scission of C-H takes place or it is the C-C bond which is broken during the course of oxidation, we have studied the oxidation of two vicinal diols viz.…”
Section: Introductionmentioning
confidence: 99%